Recent judicial developments in Singapore tort law - CHAN, Gary Kok Yew (Institutional Knowledge at Singapore Management University, 2020)
This article examines the most significant Singapore Court of Appeal's decisions on tort law since 2016. It covers the torts of negligence, defamation, harassment, economic torts and malicious prosecution as well as the damages recoverable. The main issues discussed by the Singapore Court of Appeal were as follows:What should be the scope of duty of care for claims in negligence? How do we ensure legal certainty and coherence in its application to the myriad contexts?What is the standard of care expected of medical doctors in respect of the advice to be communicated by doctors to their patients?In what circumstances can we accommodate new heads of damages in negligence?How do we determine the quantum of damages recoverable with respect to the defence of contributory negligence?What is the distinction between statements deserving of absolute versus qualified privilege?In what circumstances may a director be protected from personal liability with respect to company torts?Should the tort of malicious prosecution extend to civil proceedings? Should we recognise the tort of abuse of process?Should punitive damages be allowed and if so, what is the permitted scope?